Structural Behaviors of Reinforced Concrete Piers Rehabilitated with FRP Wraps - Junsuk Kang (International Journal of Polymer Science)
The use of fiber-reinforced polymer (FRP) wraps to retrofit and strengthen existing structures such as reinforced concrete piers is becoming popular due to the higher tensile strength, durability, and flexibility gained and the method’s ease of handling and low installation and maintenance costs. As yet, however, few guidelines have been developed for determining the optimum thicknesses of the FRP wraps applied to external surfaces of concrete or masonry structures. In this study, nonlinear pushover finite element analyses were utilized to analyze the complex structural behaviors of FRP-wrapped reinforced rectangular piers. Design parameters such as pier section sizes, pier heights, pier cap lengths, compressive strengths of concrete, and the thicknesses of the FRP wraps used were thoroughly tested under incremental lateral and vertical loads. The results provide useful guidelines for analyzing and designing appropriate FRP wraps for existing concrete piers.